Securities Bankruptcy Due to Failure to Make Payments in Repurchase Agreement Transactions - Riansyah, Wildan; Kusumaningrum, Adi; Chanifah, Nur (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The Central Jakarta Commercial Court granted the request for bankruptcy to a securities company, PT. AAA Securitas requested by individuals, in this case individuals are GM and AGH through Decision No. 08/Pdt.Sus.PAILIT/2015/ PN.Niaga.Jkt.Pst. The Central Jakarta Commercial Court then decided upon the request of bankruptcy requested by GM as Petitioner I and AGH as Petitioner II granted and issued Decision No. 08 / Pdt.Sus.PAILIT / 2015 / PN.Niaga.Jkt.Pst by looking to see Article 2 paragraph (1) of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations and Article 8 paragraph (4) of Law Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, the Central Jakarta Commercial Court granted the bankruptcy application completely and canceled the bankruptcy status for PT. Andalan Artha Advisido Sekuritas. This type of research used is normative research which is theoretical by interpreting and examining the application of the rules concerning conceptions, principles, doctrines and norms in positive law in force. Based on the results of the study it was found that the ruling was contrary to the provisions of Article 2 paragraph (4) of the Bankruptcy Law and SDPO because the party who has the right to submit a request for bankruptcy against PT. AAA Securities are Financial Services Authority (Otoritas Jasa Keuangan/OJK).